Ultralow-viscosity lithium iron manganese phosphate material and preparation method thereof, lithium battery and electric equipment

By pre-synthesis of ferromanganese phosphate precursor and adding carbon source in two steps, the problems of high viscosity and easy manganese dissolution of lithium manganese phosphate materials are solved, and the circulation performance and high-temperature storage performance of lithium batteries are improved.

CN119176537AInactive Publication Date: 2024-12-24HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD

Patent Information

Application Number
CN202411688829.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high viscosity of lithium manganese ferrophosphate materials and the easy dissolution of manganese lead to poor circulation performance of lithium-ion batteries. The existing nano-treatment treatment methods lead to an increase in ultra-fine powder, an increase in the specific surface area of ​​the material, and a low compaction density, further reducing battery performance.

Method used

By adding manganese, iron, phosphorus, dispersant and carbon source to deionized water for mixed grinding, calcining and sintering, the precursor of manganese phosphate is pre-synthesized, the distribution and particle size of ferromanganese phosphate are controlled, and carbon is added in two steps. Source to form a cladding layer and use a viscosity regulator to adjust the material viscosity, enhancing the stability and conductivity of the material.

Benefits of technology

The preparation of ultra-low viscosity lithium manganese iron phosphate material is realized, which improves the electrochemical performance and cyclic stability of the material, reduces the dissolution rate of manganese, and improves the actual capacity and high-temperature storage performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176537A_ABST
    Figure CN119176537A_ABST
Patent Text Reader

Abstract

The invention discloses an ultralow-viscosity lithium iron manganese phosphate material and a preparation method thereof, a lithium battery and electric equipment, and belongs to the technical field of lithium ion batteries. In the preparation process, a manganese iron phosphate precursor is synthesized in advance, a carbon source is added in the synthesis process, and the carbon source as a reducing agent can effectively maintain metal ions to be kept in a divalent stable state, so that the lithium iron manganese phosphate material is prepared. Therefore, the particle size can be better controlled, and the diffusion path of lithium ions is improved; and then a carbon source is added again to form a coating layer on the surface of the lithium manganese iron phosphate material, so that the conductivity and the consistency of the material can be improved. In the preparation process, a viscosity modifier is also added, so that the generated ultrafine powder can be dissolved, the excessive nanocrystallization of the material is avoided, the dissolution of manganese is inhibited, the structural stability is favorably maintained, meanwhile, the surface appearance of the material can be modified, the specific surface area and viscosity of the material are effectively reduced, and the processing performance is excellent; and the cycle performance and the high-temperature storage performance of the material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to ultra-low viscosity lithium manganese iron phosphate materials and preparation methods, lithium batteries, and electrical equipment. Background Art

[0002] Lithium iron manganese phosphate (LiFeMnPO4, LFMP for short) is a new generation of lithium-ion battery positive electrode material with multiple characteristics such as high energy density, high safety, low cost and green environmental protection. It is widely used in new energy vehicles and energy storage fields.

[0003] As cathode materials for lithium-ion batteries, lithium iron phosphate and lithium iron phosphate have the same high theoretical capacity, but the Li + / Li electrode potential is much higher than that of lithium iron phosphate, and as a positive electrode material, it is located in the stable electrochemical window of the organic electrolyte system. The high potential property makes lithium manganese iron phosphate have a potential high energy density advantage. Compared with lithium iron phosphate, it can better adapt to the continuous expansion of the lithium-ion battery market and the rapid development of the energy storage field, and meet the current demand for high-performance, low-cost positive electrode materials.

[0004] Although some of the performance of lithium iron manganese phosphate has been significantly enhanced compared to lithium iron phosphate, the addition of manganese has also brought some new problems. Manganese is prone to dissolution during the charging and discharging process, which will lead to poor cycle performance of lithium-ion batteries. In addition, due to the poor conductivity of lithium iron manganese phosphate materials, especially for some lithium iron manganese phosphate materials with high manganese content, the actual capacity is quite different from the theoretical capacity. In order to improve the electrical properties of lithium iron manganese phosphate, the existing preparation process usually adopts nano-processing to shorten the lithium ion deintercalation path by reducing the particle size, thereby increasing the actual capacity. However, excessive nano-processing will bring about problems such as an increase in the proportion of ultrafine powder, an increase in the specific surface area of ​​the material, and a low compaction density, resulting in high viscosity and severe water absorption during processing. In addition, excessive nano-processing will also aggravate the dissolution of manganese, further reducing the cycle performance of lithium-ion batteries.

[0005] Therefore, there is an urgent need to develop a lithium manganese iron phosphate material with ultra-low viscosity characteristics, which can solve the problems of high viscosity and manganese dissolution, and improve the overall performance of the lithium manganese iron phosphate material. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-low viscosity lithium iron manganese phosphate material and a preparation method, a lithium battery, and electrical equipment to solve the problem that the lithium iron manganese phosphate material has high viscosity and easy dissolution of manganese.

[0007] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing an ultra-low viscosity lithium manganese iron phosphate material, comprising the following steps: S1. Add manganese source, iron source, phosphorus source, dispersant and carbon source into deionized water, mix well, grind for the first time, heat and evaporate, dry, calcine under nitrogen atmosphere, and finally crush to obtain manganese iron phosphate precursor Fe x Mn (1-x) PO4 and 0.10<x<0.90; S2. The ferromanganese phosphate precursor, the lithium source, the carbon source, the cationic dopant and the deionized water are mixed and then ground for a second time to obtain a premix; S3. Add viscosity regulator to deionized water, mix and disperse uniformly, then add to the premixed liquid and continue grinding. After drying, sintering and air flow milling, ultra-low viscosity lithium manganese iron phosphate material is obtained.

[0008] Preferably, the manganese source includes a combination of one or more of manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate, manganese phosphate, manganese dichloride and manganese sulfate.

[0009] Preferably, the iron source includes one or more combinations of iron powder, reduced iron powder, iron oxide, iron nitrate, ferrous oxalate dihydrate, ferrosoferric oxide, ferric carbonate and ferric phosphate.

[0010] Preferably, the phosphorus source includes one or more combinations of phosphoric acid, lithium phosphate, lithium hydrogen phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, iron phosphate, manganese phosphate, sodium phosphate, dipotassium hydrogen phosphate, pyrophosphoric acid and sodium pyrophosphate.

[0011] Preferably, the process parameters of the primary grinding are: ball mill speed 400-650 r / min, grinding time 1-3 h, and particle size D50 after grinding is 1.0-2.5 μm.

[0012] Preferably, heating evaporation is used to remove the solvent, and the evaporation temperature is 150-250°C.

[0013] Preferably, the drying is carried out in a vacuum environment at a drying temperature of 100-150°C.

[0014] Preferably, the calcination process parameters are: calcination temperature 500-650° C., constant temperature calcination time 4-6 hours.

[0015] Preferably, the lithium source includes a combination of one or more of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium hydroxide, lithium carbonate, lithium oxalate, lithium chloride, lithium acetate and lithium phosphate; the molar ratio of the lithium source to the ferromanganese phosphate precursor is (0.95-1.15): (0.95-1.18).

[0016] Preferably, the process parameters of the secondary grinding are: ball mill speed 1500-2200 r / min, grinding time 1-2.5 h, and particle size D50 after grinding is 250-400 nm.

[0017] Preferably, the drying is one of centrifugal spray drying and airflow spray drying; the inlet air temperature of the spray drying is 180-260°C, and the outlet air temperature is 90-110°C.

[0018] Preferably, the sintering process parameters are: sintering atmosphere is nitrogen atmosphere, heating rate is 1-10° C. / min, sintering temperature is 700-850° C., and constant temperature sintering time is 6-12 h.

[0019] By adopting the above technical solution, the present invention can ensure the uniform distribution of manganese iron elements in the material by pre-synthesizing the manganese iron phosphate precursor, and can accurately control the ratio between iron atoms and manganese atoms in the material, so that the manganese iron ratio in the final manganese iron phosphate lithium material is wider, thereby meeting the needs of different scenarios and performances. In addition, the pre-synthesis of the precursor can better control the size and morphology of the formed particles, improve the diffusion path of lithium ions, and thus improve the electrochemical performance of the material.

[0020] At the same time, the present invention adds the carbon source in two steps and processes the lithium manganese iron phosphate material respectively, which can regulate the valence state of each element in the precursor synthesis process to be consistent, avoid the generation of other impurities that affect the material performance, and reduce the dissolution of manganese. In addition, after the secondary grinding, the density of the carbon coating layer is improved, and the consistency of the material is improved.

[0021] The present invention also adds a viscosity regulator to adjust the viscosity of the material, which can dissolve the ultrafine powder produced in the preparation process and modify the morphology of the lithium manganese iron phosphate material particles to avoid the increase in material viscosity and the dissolution of manganese due to the presence of ultrafine powder. Without affecting the electrical properties of the material, the specific surface area of ​​the material and the dissolution probability of manganese are reduced, and the stability of the material is improved, thereby improving the cycle performance and high-temperature storage performance of the obtained lithium battery.

[0022] Finally, the present invention ensures that the size of the lithium manganese iron phosphate material is within a controllable range to the greatest extent by adjusting and controlling the process parameters of each link, thereby increasing the actual capacity and reducing the viscosity of the material.

[0023] Preferably, the dispersant includes a combination of one or more of citric acid, succinic acid, tripropyl phosphate, dibutyl phosphate, polyamide-based silicone oil, methylcyclosiloxane, sodium dodecylbenzene sulfonate and sodium octylbenzene sulfonate; the mass ratio of the dispersant to the iron source is (0.002-0.03):1.

[0024] By adopting the above technical scheme, the dispersant selected by the present invention is a polymer dispersant. During the synthesis of the ferromanganese phosphate precursor, the polymer dispersant can be adsorbed on the surface of the formed solid particles to form an adsorption layer, which brings additional charges to the surface of the solid particles and increases the number of surface charges, thereby enhancing the electrostatic repulsion between the particles, preventing the particles from agglomerating, and helping to form a smaller and more uniform lithium ferromanganese phosphate material. At the same time, the increase in the number of charges is conducive to better adsorption and fixation of the carbon source, forming a uniform conductive network, and providing more active sites for the lithium ferromanganese phosphate material, which is conducive to the deintercalation of lithium ions during the charge and discharge process, increasing the diffusion rate of lithium ions, and improving the conductivity and cycle stability of the lithium battery.

[0025] In addition, since the dispersant has a large molecular weight, the molecular chain can fully stretch in the deionized water medium to form a layered structure. The resulting steric hindrance effect can prevent the solid particles from approaching and agglomerating with each other, further promoting the uniform dispersion of the solid particles in the deionized water, and avoiding the agglomeration of the solid particles, which leads to a larger particle size of the final lithium manganese iron phosphate material and reduces the capacity of the positive electrode material.

[0026] Preferably, the carbon source includes a combination of one or more of starch, glucose, sucrose, molasses, corn flour, organic acid, carbonate, citric acid, sodium acetate, polyethylene, polyethylene glycol and polyvinyl alcohol; the mass ratio of the carbon source to the iron source in step S1 is (0.002-0.05):1; the mass ratio of the carbon source to the manganese iron phosphate precursor in step S2 is (0.008-0.03):1.

[0027] By adopting the above technical scheme, the carbon source of the present invention is added in two steps. The main purpose of adding the carbon source in the preparation process of the ferromanganese phosphate precursor is to use the carbon source as a reducing agent to reduce the metal ions in the system, thereby effectively maintaining the manganese ions and iron ions in a divalent stable state, thereby ensuring the uniformity and stability of the valence state of the elements in the system, effectively avoiding the introduction of other impurities into the precursor, and reducing the dissolution of manganese during the use of the material.

[0028] In step S3, the main purpose of adding the carbon source again in the process of adding the lithium source to form the lithium iron manganese phosphate material is to use the carbon source as a coating layer of the lithium iron manganese phosphate material. After sintering, the carbon source can form a dense and uniform coating layer on the surface of the material. The conductivity of the lithium iron manganese phosphate material after coating is significantly improved, and the powder resistivity is reduced. As a positive electrode material, it can significantly improve the electrical performance of lithium batteries.

[0029] Preferably, the cationic dopant includes a combination of one or more of titanium dioxide, vanadium pentoxide, aluminum oxide, magnesium oxide, cobalt oxide, calcium oxide, calcium carbonate and niobium trioxide; the molar ratio of the cationic dopant to the manganese iron phosphate precursor is (0.001-0.005):1.

[0030] By adopting the above technical solution, the cationic dopant is added together with the lithium source. The cationic dopant is mainly a compound containing other metal cations. In the medium, the metal cations will replace some atoms in the original structure of the lithium iron manganese phosphate material, thereby introducing lattice defects. These small defects can widen the diffusion channel of lithium ions and help the deintercalation of lithium ions during the charging and discharging process. Therefore, the number of lithium ions involved in charging and discharging also increases, thereby improving the conductivity and specific capacity of the lithium iron manganese phosphate material.

[0031] Preferably, the viscosity modifier is a mixture of anionic salt and polycarboxyl polymer in a mass ratio of (1-3):1; the molar ratio of the viscosity modifier to the ferromanganese phosphate precursor is (0.005-0.03):1.

[0032] Preferably, the anion salt comprises a combination of one or more of phosphate, borate, tungstate and nitrate; and the carboxyl polymer comprises a combination of one or more of polyacrylic acid, ammonium polyacrylate, polycarboxylate ether and polycarboxylate ester.

[0033] More preferably, the phosphate includes a combination of one or more of lithium dihydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, trisodium phosphate and disodium dihydrogen pyrophosphate; the borate includes a combination of one or more of sodium borate, sodium tetraborate and ammonium borate; the tungstate includes a combination of one or more of sodium tungstate, ferrous tungstate and ammonium tungstate; the nitrate includes a combination of one or more of ammonium nitrate, sodium nitrate and ferric nitrate.

[0034] Preferably, the molecular weight of the carboxyl polymer is 100-1500.

[0035] By adopting the above technical solution, the present invention further adjusts the viscosity of the lithium iron manganese phosphate material by adding a viscosity modifier at the end. The viscosity modifier of the present invention is obtained by combining an anion salt and a carboxyl polymer. After the anion salt is dissolved in deionized water, a large amount of H + Its acidity can dissolve the ultrafine powder (<100nm) produced by the secondary grinding process of lithium manganese iron phosphate material. Compared with ordinary lithium manganese iron phosphate particles, ultrafine lithium manganese iron phosphate material particles have a significantly larger specific surface area, and the gaps between particles are also reduced, resulting in a greatly increased reactivity of ultrafine particles, which can react with H, which also has strong reactivity. + This can reduce the viscosity of the material while reducing the content of ultrafine powder in the material, avoid excessive nano-sizing of lithium manganese iron phosphate materials, further inhibit the dissolution of manganese, improve the overall particle size distribution of the material, and thus improve the specific capacity and various properties of the positive electrode material.

[0036] The addition of carboxyl polymer can adjust the viscosity and fluidity of the material slurry, which helps to solve the problems of thickening, freezing and gelation of lithium manganese iron phosphate material slurry caused by the presence of ultrafine powder. This is conducive to the H generated by anionic salts. + Uniform dispersion in the material improves the efficiency of dissolving ultrafine powder. In addition, by modifying the surface morphology of lithium iron manganese phosphate material, the material can be dispersed secondary to make the distribution of the material more uniform, which is conducive to the uniformity of the crystallinity and uniform distribution of the crystals of lithium iron manganese phosphate material after sintering.

[0037] At the same time, the molecular structure of the carboxyl polymer is simple, containing only three elements: carbon, hydrogen, and oxygen. It does not contain other metal elements and will not introduce other metal impurities during the final sintering, thereby affecting the conductive properties of the lithium manganese iron phosphate material.

[0038] Furthermore, when the molecular weight of the carboxyl polymer is less than 1500, the low molecular weight carboxyl polymer is more conducive to subsequent material processing and does not affect the grinding process; and the low molecular weight carboxyl polymer has good dispersion effect, good dispersion stability, and good flowability in the medium, which can accelerate the dispersion of solid particles in the viscosity regulator solution and the dissolution of ultrafine powder, thereby improving the uniformity of the solid particles of the lithium manganese iron phosphate material.

[0039] Preferably, in step S3, the center temperature of the material discharged from the furnace after sintering is 100-200°C.

[0040] By adopting the above technical solution, during the process of sintering to obtain lithium iron manganese phosphate material, the temperature of the material discharged from the furnace after sintering is controlled. When the material temperature is higher than 200°C, the material has a certain oxidation risk, and the iron ions therein are easily oxidized to iron oxide. The increase in the iron oxide content in the lithium iron manganese phosphate material will cause the content of iron ions that can participate in the charging and discharging process in the lithium iron manganese phosphate material to decrease, which will reduce the specific capacity of the material and there is a certain low capacity risk.

[0041] In a second aspect, the present invention provides an ultra-low viscosity lithium manganese iron phosphate material, which is prepared according to the above-mentioned method for preparing the ultra-low viscosity lithium manganese iron phosphate material.

[0042] By adopting the above technical scheme, the ultra-low viscosity lithium manganese iron phosphate material prepared according to the above preparation method has uniform particle size distribution, uniform particle size, high material consistency, low viscosity, effectively improves the dissolution of manganese, has high actual specific capacity, and has good conductivity and cycle performance.

[0043] In a third aspect, the present invention provides a lithium battery, wherein the positive electrode material of the lithium battery adopts the ultra-low viscosity lithium manganese iron phosphate material prepared as above.

[0044] In a fourth aspect, the present invention provides an electrical device, the electrical device comprising the lithium battery obtained above.

[0045] Beneficial effects of the present invention: 1. The method for preparing ultra-low viscosity lithium iron manganese phosphate material provided by the present invention is simple to operate, and the raw material source is wide. The mass ratio between manganese and iron atoms in the prepared material is controllable and evenly distributed in the material. The pre-prepared manganese iron phosphate precursor can better control the particle size, improve the diffusion path of lithium ions and thus improve the electrical properties of the material. In addition, the process equipment of the present method is compatible with the lithium iron phosphate process equipment, which can reduce the equipment cost.

[0046] 2. In the present invention, the carbon source is added twice. The addition of the carbon source during the preparation of the ferromanganese phosphate precursor can be used to reduce the metal ions in the system, effectively maintaining the manganese ions and iron ions in a divalent stable state, and avoiding the generation of other impurities. When the carbon source is added together with the lithium source to form the lithium ferromanganese phosphate material, the carbon source is coated on the surface of the material to increase the conductivity of the material, and the coating layer is dense and uniform with good consistency.

[0047] The viscosity regulator used in the present invention can dissolve the ultrafine powder produced in the material preparation process, avoid excessive nano-sizing of the material, inhibit the dissolution of manganese, and is conducive to maintaining structural stability. At the same time, it also modifies the surface morphology of the material particles, effectively reduces the specific surface area and viscosity performance, has excellent processing performance, and effectively improves the material's circulation performance and high-temperature storage performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The present invention will be further described below in conjunction with the accompanying drawings.

[0049] Figure 1 is a scanning electron microscope image of the ultra-low viscosity lithium manganese iron phosphate material obtained in Example 1 of the present invention, wherein the magnification is 10000; Figure 2 This is a scanning electron microscope image of the ultra-low viscosity lithium manganese iron phosphate material obtained in Example 1 of the present invention, wherein the magnification is 50,000. DETAILED DESCRIPTION

[0050] Example Example 1, an ultra-low viscosity lithium manganese iron phosphate material is prepared according to the following method: A manganese source, an iron source, a phosphorus source, a dispersant and a carbon source are added to deionized water, wherein the manganese source is manganese carbonate, the iron source is ferric nitrate, and the phosphorus source is phosphoric acid. The molar ratio of the manganese source, the iron source and the phosphorus source is set to 0.6:0.4:1. The dispersant is sodium dodecylbenzene sulfonate, and the mass ratio of sodium dodecylbenzene sulfonate to the iron source is 0.01:1. The carbon source is citric acid, and the mass ratio of citric acid to the iron source is 0.04:1. The solid content of the mixture is 40%; after mixing evenly, it is ground once at a speed of 500r / min for 1.5h, and then heated to evaporate the deionized water, and the heating evaporation temperature is 200°C, and then the obtained solid mixture is dried in a vacuum environment, and the drying temperature is set to 120°C, and the drying time is 12h. After drying, it is calcined in a nitrogen atmosphere, and the calcination temperature is set to 600°C, and the calcination time is 5h. Finally, after roller crushing, a manganese iron phosphate precursor Fe is obtained. 0.4 Mn 0.6 PO4; A ferromanganese phosphate precursor, a lithium source, a carbon source, a cationic dopant and deionized water are mixed to obtain a mixture having a solid content of 40%, wherein the lithium source is lithium hydroxide, and the mass ratio of the lithium source to the ferromanganese phosphate precursor is 1.03:1; the carbon source is polyethylene glycol, and the mass ratio of the polyethylene glycol to the ferromanganese phosphate precursor is 0.015:1; the cationic dopant is vanadium pentoxide, and the molar ratio of the vanadium pentoxide to the ferromanganese phosphate precursor is 0.0026:1; and a premix is ​​obtained by secondary grinding at a speed of 2000 r / min for 1 h; Weigh anionic salt and carboxyl polymer in a mass ratio of 1:1, mix to obtain a viscosity modifier, wherein the anionic salt is sodium dihydrogen phosphate, and the carboxyl polymer is polyacrylic acid with an average molecular weight of 1200. Add the viscosity modifier to deionized water, stir and mix until the deionized water is completely clarified, use a dispersing emulsifier to homogenize for 0.5h, then add it to the premixed liquid and continue grinding for 1h, wherein the molar ratio of the viscosity modifier to the manganese iron phosphate precursor is 0.02:1, then after centrifugal spray drying at 230℃, place it in a nitrogen atmosphere for sintering at 800℃ for 8h, control the center temperature of the material out of the furnace to be 150℃, and finally obtain the ultra-low viscosity manganese iron phosphate lithium material through air flow crushing. The morphology of the ultra-low viscosity manganese iron phosphate lithium material can be seen Figure 1 and Figure 2 Scanning electron microscope image of .

[0051] Example 2, an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that the molar ratio of the manganese source, the iron source and the phosphorus source is 0.2:0.8:1, and the manganese iron phosphate precursor Fe 0.8 Mn 0.2 PO4, the mass ratio of sodium dodecylbenzene sulfonate to the iron source is 0.002:1, the mass ratio of citric acid to the iron source is 0.002:1, and the calcination temperature is set to 500°C and the calcination time is 6h.

[0052] Example 3, an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that the molar ratio of the manganese source, the iron source and the phosphorus source is 0.8:0.2:1, and the manganese iron phosphate precursor Fe 0.2 Mn 0.8 PO4, the mass ratio of sodium dodecylbenzene sulfonate to the iron source is 0.03:1, the mass ratio of citric acid to the iron source is 0.05:1, and the calcination temperature is set to 650°C and the calcination time is 4h.

[0053] Example 4, an ultra-low viscosity lithium iron manganese phosphate material, differs from Example 1 only in that the mass ratio of the lithium source to the iron manganese phosphate precursor is 0.95:1, the mass ratio of polyethylene glycol to the iron manganese phosphate precursor is 0.008:1, the molar ratio of vanadium pentoxide to the iron manganese phosphate precursor is 0.001:1, and the sintering temperature is set to 700°C and the sintering time is 12 hours.

[0054] Example 5, an ultra-low viscosity lithium iron manganese phosphate material, differs from Example 1 only in that the mass ratio of the lithium source to the iron manganese phosphate precursor is 1.15:1, the mass ratio of polyethylene glycol to the iron manganese phosphate precursor is 0.03:1, the molar ratio of vanadium pentoxide to the iron manganese phosphate precursor is 0.005:1, and the sintering temperature is set to 850°C and the sintering time is 6 hours.

[0055] Example 6, an ultra-low viscosity lithium manganese iron phosphate material, is different from Example 1 only in that the viscosity modifier is a mixture of sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 2:1; the molar ratio of the viscosity modifier to the lithium manganese iron phosphate precursor is 0.01:1.

[0056] Example 7, an ultra-low viscosity lithium manganese iron phosphate material, differs from Example 1 only in that the viscosity modifier is a mixture of sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 3:1; the molar ratio of the viscosity modifier to the lithium manganese iron phosphate precursor is 0.03:1.

[0057] Example 8, an ultra-low viscosity lithium manganese iron phosphate material, differs from Example 1 only in that the viscosity regulator obtained by mixing equal amounts of sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 1:1 is replaced by a viscosity regulator obtained by mixing equal amounts of sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 0.5:1.

[0058] Example 9, an ultra-low viscosity lithium manganese iron phosphate material, differs from Example 1 only in that the viscosity regulator obtained by mixing equal amounts of sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 1:1 is replaced by a viscosity regulator obtained by mixing equal amounts of sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 4:1.

[0059] Example 10, an ultra-low viscosity lithium manganese iron phosphate material, is different from Example 1 only in that the molar ratio of the viscosity modifier to the lithium manganese iron phosphate precursor is 0.002:1.

[0060] Example 11, an ultra-low viscosity lithium manganese iron phosphate material, is different from Example 1 only in that the molar ratio of the viscosity modifier to the lithium manganese iron phosphate precursor is 0.04:1.

[0061] Example 12, an ultra-low viscosity lithium manganese iron phosphate material, is different from Example 1 only in that the polyacrylic acid with an average molecular weight of 1200 is replaced by an equal amount of polyacrylic acid with an average molecular weight of 2000.

[0062] Example 13, an ultra-low viscosity lithium manganese iron phosphate material, differs from Example 1 only in that an equal amount of polyacrylic acid (average molecular weight of 1200) is used as a viscosity regulator to replace the viscosity regulator obtained by mixing sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 1:1.

[0063] Example 14, an ultra-low viscosity lithium manganese iron phosphate material, is different from Example 1 only in that an equal amount of sodium dihydrogen phosphate is used as a viscosity regulator to replace the viscosity regulator obtained by mixing sodium dihydrogen phosphate and polyacrylic acid (average molecular weight of 1200) in a mass ratio of 1:1.

[0064] Comparative Example Comparative Example 1 is an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that no dispersant is added.

[0065] Comparative Example 2 is an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that no carbon source is added during the preparation of the lithium manganese iron phosphate precursor.

[0066] Comparative Example 3 is an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that no cationic dopant is added.

[0067] Comparative Example 4 is an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that no carbon source is added during the secondary grinding process of the lithium manganese iron phosphate material.

[0068] Comparative Example 5 is an ultra-low viscosity lithium manganese iron phosphate material, which is different from Example 1 only in that no viscosity regulator is added.

[0069] Performance testing 1. Physical and chemical properties test of lithium manganese iron phosphate material: (1) Carbon content: The carbon content (%) of the ultra-low viscosity ferromanganese phosphate materials obtained in the examples and comparative examples was tested by elemental analysis.

[0070] (2) Specific surface area: The specific surface area (m2) of the ultra-low viscosity ferromanganese phosphate materials obtained in the examples and comparative examples was measured using a specific surface area tester. 2 / g).

[0071] (3) Viscosity: The lithium manganese iron phosphate material obtained in the example and the comparative example was mixed with the conductive carbon powder and the PVDF binder in a mass ratio of 90:5:5, and the viscosity (mPa·s) of the mixture was measured using a rotational viscometer.

[0072] The above test results are shown in Table 1.

[0073] 2. Electrical performance test: Battery assembly: The lithium manganese iron phosphate material obtained in the embodiment and the comparative example is used as the battery positive electrode material, mixed with conductive carbon powder and PVDF binder in a mass ratio of 90:5:5, and then coated on an aluminum foil sheet after homogenization. After drying, it is rolled with a double-roller machine, and then the positive electrode sheet is obtained by a punching machine. The negative electrode sheet is a lithium sheet, and a CR2032 button battery is obtained after assembly.

[0074] Under constant temperature of 25℃, in the operating voltage range of 2.0~3.8V, the specific capacity (mAh / g) of the battery was tested at 1C and 0.1C rates respectively.

[0075] The above test results are shown in Table 2.

[0076]

[0077]

[0078] Combining Example 1 and Example 2 to Example 7, it can be seen that the physical and chemical properties and electrical properties of Example 2 to Example 7 are not significantly changed compared with Example 1. The reason is that the difference between Example 2 to Example 7 and Example 1 is only that the ratio of raw materials in the preparation process of lithium manganese iron phosphate material is changed within the required range, which has no significant effect on the performance of the final lithium manganese iron phosphate.

[0079] In combination with Example 1, Example 8 and Example 9, Example 13 and Example 14, it can be seen that the various properties of Example 8 and Example 9 as well as Example 13 and Example 14 are reduced compared with Example 1. Specifically, the carbon content of Example 8 increases, and the specific surface area and viscosity increase. The reason is that the viscosity regulator in Example 8 reduces the amount of anionic salt added, the proportion of carboxyl polymer increases, thereby increasing the carbon content, and the number of molecules attached to the surface of the material increases, thereby increasing the specific surface area of ​​the particles, and the electrical properties decrease accordingly; in Example 13, no anionic salt is added, and the performance decreases more significantly. The lack of anionic salt dissolving effect on the ultrafine powder in the material causes the viscosity of the material to increase significantly, affecting the electrical properties of the material. The viscosity regulator in Example 9 increases the amount of anionic salt added, lacks the dispersing effect of the carboxyl polymer on the solid particles of the lithium iron manganese phosphate material, and the dispersibility of the material particles is greatly reduced. The anionic salt is difficult to react with the ultrafine powder, and lacks the modification of the surface morphology of the lithium iron manganese phosphate material by the carboxyl polymer. The electrical properties of the material are also significantly reduced. In Example 14, the viscosity regulator is only anionic salt, and the material performance is more significantly reduced.

[0080] Combining Example 1, Example 10 and Example 11, it can be seen that the viscosity of Example 10 increases and the electrical properties decrease compared with Example 1, and the carbon content of Example 11 increases and the electrical properties decrease compared with Example 1. The reason is that the difference between Example 10 and Example 11 compared with Example 1 is only that the amount of viscosity modifier added is adjusted. In Example 10, the amount of viscosity modifier added is reduced, the dissolution effect of the anion salt on the ultrafine powder decreases, the viscosity of the material increases, and the performance decreases; in Example 11, the amount of viscosity modifier added is increased, and the content of carboxyl polymer in the system is also increased. The increase of polymer is not conducive to the improvement of material dispersibility and processability, and is not conducive to the dissolution effect of the anion salt, thereby causing the electrical properties of the material to decrease.

[0081] Combining Example 1 and Example 12, it can be seen that the carbon content and viscosity of Example 12 are increased, and the electrical properties are decreased compared with Example 1. The reason is that the difference between Example 12 and Example 1 is only that the molecular weight of the carboxyl polymer in the viscosity regulator of Example 12 is greater than 1500. Too large a molecular weight is not conducive to the dispersion and stability of the lithium iron manganese phosphate material. The agglomeration of ultrafine powders will affect the dissolution of anion salts, reduce the fluidity of the material, and be unfavorable to the uniformity of the particle size of the lithium iron manganese phosphate material, and the performance of the obtained material will also decrease accordingly.

[0082] Combining Example 1 and Comparative Examples 1 to 5, it can be seen that the various properties of Comparative Examples 1 to 5 are significantly reduced compared to Example 1. Specifically, Comparative Example 1 does not add a dispersant compared to Example 1, which will result in a significant decrease in the dispersibility of the solid particles formed during the preparation of the ferromanganese phosphate precursor, and the agglomeration will affect the uniform distribution of the particle size of the material. The larger the particle size, the lower the specific capacity when it is used as a positive electrode material; the difference between Comparative Example 2 and Example 1 is that no carbon source is added during the preparation of the ferromanganese phosphate precursor, and the lack of a carbon source as a reducing agent makes it difficult for the various elements in the system, especially the manganese element, to maintain a divalent stable state and easily disproportionate to other valence states, affecting the stability of the ferromanganese phosphate precursor, and aggravating the dissolution of manganese in the obtained lithium iron manganese phosphate material, thereby affecting the material. The electrical properties of the material are improved; compared with Example 1, no cationic dopant is added in Comparative Example 3, the diffusion channel of lithium ions is reduced, and the electrical properties are reduced; in Comparative Example 4, no carbon source is added in the preparation of the lithium iron manganese phosphate material. The lack of a carbon source as a material coating layer will significantly reduce the conductivity of the material, the consistency of the particle size is also reduced, and the material performance is reduced; compared with Example 1, no viscosity regulator is added in Comparative Example 5. On the one hand, the lack of anionic salt to dissolve the ultrafine powder will lead to excessive nano-sizing of the lithium iron manganese phosphate material, aggravate the dissolution of manganese, and affect the viscosity of the material; on the other hand, the lack of carboxyl polymer to disperse the material and modify the surface morphology, the dispersibility, fluidity, crystallinity and particle size consistency of the material are reduced, resulting in a significant increase in the viscosity of the material, thereby affecting the electrical properties of the material.

[0083] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an ultra-low viscosity lithium manganese iron phosphate material, characterized in that: The following steps are involved: S1. Add a manganese source, an iron source, a phosphorus source, a dispersant and a carbon source to deionized water, mix well, grind for the first time, heat and evaporate, dry, calcine under a nitrogen atmosphere, and finally crush to obtain a manganese iron phosphate precursor FexMn(1-x)PO4 with 0.10<x<0.90; S2. The ferromanganese phosphate precursor, the lithium source, the carbon source, the cationic dopant and the deionized water are mixed and then ground for a second time to obtain a premix; S3. Add viscosity regulator to deionized water, mix and disperse uniformly, then add to the premixed liquid and continue grinding. After drying, sintering and air flow milling, ultra-low viscosity lithium manganese iron phosphate material is obtained.

2. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 1, characterized in that: The dispersant includes a combination of one or more of citric acid, succinic acid, tripropyl phosphate, dibutyl phosphate, polyamide-based silicone oil, methylcyclosiloxane, sodium dodecylbenzene sulfonate and sodium octylbenzene sulfonate; the mass ratio of the dispersant to the iron source is (0.002-0.03):

1.

3. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 1, characterized in that: The carbon source comprises a combination of one or more of starch, glucose, sucrose, molasses, corn flour, organic acid, carbonate, citric acid, sodium acetate, polyethylene, polyethylene glycol and polyvinyl alcohol; the mass ratio of the carbon source to the iron source in step S1 is (0.002-0.05):1; the mass ratio of the carbon source to the manganese iron phosphate precursor in step S2 is (0.008-0.03):

1.

4. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 1, characterized in that: The cationic dopant includes a combination of one or more of titanium dioxide, vanadium pentoxide, aluminum oxide, magnesium oxide, cobalt oxide, calcium oxide, calcium carbonate and niobium trioxide; the molar ratio of the cationic dopant to the ferromanganese phosphate precursor is (0.001-0.005):

1.

5. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 1, characterized in that: The viscosity modifier is a mixture of anionic salt and carboxyl polymer in a mass ratio of (1-3):1; the molar ratio of the viscosity modifier to the ferromanganese phosphate precursor is (0.005-0.03):

1.

6. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 5, characterized in that: The anion salt includes one or more combinations of phosphates, borates, tungstates and nitrates; the carboxyl polymer includes one or more combinations of polyacrylic acid, polyacrylic acid ammonium salt, polycarboxylic acid ether and polycarboxylic acid ester.

7. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 5, characterized in that: The molecular weight of the carboxyl polymer is 100-1500.

8. The method for preparing the ultra-low viscosity lithium manganese iron phosphate material according to claim 1, characterized in that: In the step S3, the center temperature of the material discharged from the furnace after sintering is 100-200°C. 9 . The ultra-low viscosity lithium iron manganese phosphate material obtained by the method for preparing the ultra-low viscosity lithium iron manganese phosphate material according to any one of claims 1 to 8 .

10. A lithium battery, characterized in that: The positive electrode material of the lithium battery is the ultra-low viscosity lithium iron manganese phosphate material as described in claim 9.

11. Electrical equipment, characterized in that: The electrical equipment comprises the lithium battery according to claim 10.

Citation Information

Patent Citations

  • Carbon-coated lithium manganese iron phosphate material, preparation method thereof and battery

    CN115744860A

  • Method for improving monodispersity of lithium iron phosphate positive electrode material particles

    CN115974038A

  • Doped, coated and modified lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN118306962A

  • Preparation method of battery composite material and precursor thereof

    US20160072129A1

Cited By

  • Lithium iron phosphate precursor slurry additive and carbon-coated lithium iron phosphate

    CN121894633A